iClass: MOBILE WEB PENDUKUNG PROGRAM BELAJAR #DiRumahAja SEBAGAI SALAH SATU UPAYA PENCEGAHAN PENULARAN COVID-19 - Bata, Emanuel Safirman (STIKOM Uyelindo Kupang, 2020)
Covid-19 is an infectious disease caused by a newly discovered type of coronavirus. This is a new virus and a disease previously unknown before the outbreak in Wuhan, China, in December 2019. To suppress its spread, at the end of 2019 the government appealed to every educational institution to implement a home study program. In this regard, the development of a learning model in the Covid-19 emergency period is now an obligation that must be done by every educator in Indonesia. Nowadays information technology plays an important role in all fields, including in education. The right learning media to use now is certainly a choice that must be made, based on information technology. The development of information and communication technology has experienced rapid development, so that it impacts on human life. This development can be seen from the pattern of technology-based education. The application of technology in education better known as Information and Communication Technology (ICT) has finally become the pulse in the world of education. It is clear that ICT has become an integrated part of learning through distance learning or internet-based learning (e-learning). During the Covid-19 emergency. at the end of 2019 after receiving an appeal from the government regarding home learning programs due to the Covid-19 pandemic, STIKOM Uyelindo Kupang felt the need to build a system to be able to help monitor online teaching and learning activities from home by utilizing internet technology or known as e-learning. The main purpose of iClass (e-learning that will be built) is to collect student attendance data online so that it can help the academic community to control lecture activities in real time. Presentation of data will be faster, more precise and accurate.